Incidence of Fungal Infection in Positive Donor Rim Cultures after Corneal Transplantation. (19th May 2022) - Shatten, Julia; Kamyar, Roheena; Dhaliwal, Deepinder; Kowalski, Regis P.; Jhanji, Vishal
ABSTRACT: Purpose: To determine the clinical outcomes of corneal transplant patients that had positive rim cultures for fungi. Methods: Retrospective study. Results: Of 1276 rim cultures obtained between 2009 and 2019, 16 were positive for fungus (incidence of 1.25%). Clinical data were available for 12 patients. Candida and Cladosporium species were the most common organisms. Recipient ages ranged from 51 to 86 (median age 69 years; 9 males, 7 females). The most common surgery was Endothelial Keratoplasty (n = 8). There were no instances of fungal keratitis or endophthalmitis. Three patients were treated with prophylactic antimycotics. One patient developed bacterial keratitis. One patient had a varicella zoster virus reactivation without corneal involvement. Conclusions: This study adds to the growing data on the low rate of fungal keratitis and endophthalmitis after a corneal transplant, even in the case of positive rim cultures. This study also suggests that positive rim cultures do not advance the risk of postoperative fungal infection in the recipient.